Study of socio-demographic, behavioural and clinical risk factors of diabetic foot in a tertiary care centre - Sachin, Idoor D.; Manasa, Megaravalli R.; Subhashree, P. (International Surgery Journal, 2021)
Background: Diabetic foot is the most devastating complication of diabetes. Diabetic foot infection is a potential limb threatening condition. Several socio-demographic, behavioural and clinical factors are responsible for higher risk of diabetic foot. Hence this study was planned with the objective to assess association between socio-demographic, behavioural and clinical risk factors and diabetic foot and response of patients to various treatment modalities. Methods: 50 patients of diabetic foot were studied over a six-month period. The diabetic foot ulcers were classified according to Wagner’s classification. Data about various socio-demographic, behavioural and clinical factors was collected. Radiological investigations, neurological examination and culture and sensitivity of ulcer discharge was done. The patients were managed by conservative or surgical management. Results: Common age group of presentation was 51-60 years. Males were more commonly affected. All participants were of low socio-economic status and majority were unskilled labourers. Tobacco (40%) and alcohol (32%) use and lack of physical activity (92%) were seen. All had diabetes of >10 years and elevated BMI. Grade 4 ulcer were the most frequent and toes were commonly involved. S. aureus was the commonest organism. Wound debridement was done in 76% patients and 34% required amputation. Conclusions: Factors like advancing age, low socio-economic status, lack of family support, occupations involving risk of trauma to foot, tobacco use, sedentary life style, and clinical factors like longer duration of diabetes, higher BMI, uncontrolled diabetes are risk factors for diabetic foot. Hence it is essential to educate the diabetic patients about these risk factors.